Model for end‐stage liver disease Na Score predicts incident major cardiovascular events in patients with nonalcoholic fatty liver disease. Issue 5 (22nd May 2017) - Simon, Tracey G.; Kartoun, Uri; Zheng, Hui; Chan, Andrew T.; Chung, Raymond T.; Shaw, Stanley; Corey, Kathleen E.
Abstract : Cardiovascular disease (CVD) is the leading cause of mortality among adults with nonalcoholic fatty liver disease (NAFLD); however, accurate tools for identifying NAFLD patients at highest CVD risk are lacking. Using a validated algorithm, we identified a retrospective cohort of 914 NAFLD patients without known CVD. Fibrosis severity was estimated using the fibrosis‐4 index. Patients were followed for 5 years for the development of a major adverse cardiovascular event (MACE); a composite of cardiovascular death, myocardial infarction, or unstable angina; urgent coronary revascularization; or stroke. Using an adjusted Cox proportional hazard regression model, NAFLD‐specific biomarkers of CVD risk were identified. Discrimination was compared to that of the Framingham Risk Score (FRS) using the area under the receiver operating characteristic curve. Among 914 patients, the mean age was 53.4 years and 60.6% were female. Over 5 years, 288 (31.5%) experienced MACE. After adjustment for traditional cardiometabolic risk factors and underlying FIB‐4 index score, each 1‐point increase in the model for end‐stage liver disease integrating sodium (MELD‐Na) was associated with a 4.2% increased risk of MACE (hazard ratio, 1.042; 95% confidence interval, 1.009‐1.075; P = 0.011). Compared to patients in the lowest MELD‐Na quartile (<7.5), those in the highest quartile (≥13.2) had a 2.2‐fold increased risk of MACE (adjusted hazard ratio, 2.21; 95% confidence interval, 1.11‐4.40; P = 0.024; P trend = 0.004). Incorporating MELD‐Na with the FRS significantly improved discrimination of future CVD risk (combined C‐statistic 0.703 versus 0.660 for the FRS alone; P = 0.040). Conclusion : Among patients with NAFLD, the MELD‐Na score accurately stratifies the risk for patients according to future CVD event risk. The addition of the MELD‐Na score to the FRS may further improve discrimination of NAFLD‐related CVD risk. ( Hepatology Communications 2017;1:429–438)